ECONOMIC IDEAS OF ANCIENT EGYPTIAN WORK "AHTOY’S PRECEPT, DUAUF’S SON, TO HIS SON PIOPY" - Литвин, О. Ю.; Панченко, О. П. (Scientific Progress & Innovations, 2014)
The basic economic ideas of ancient Egyptian work "Ahtoy’s precept, Duauf’s son, to his son Piopy" were considered. Publications of ukrainian and russian researchers, historians and journalists devoted to the study of this problem were analyzed. We prove relevance and significance of economic ideas of ancient Egyptian work, we focus attention on their impact on the contemporary economy. We give the facts, which support the eduction of a high level of economic development of ancient Egypt. The attention of readers we draw on the economic ideas of this ancient Egyptian works should be considered not only in the context of economic history and the history of economic thought, but also to use them.